2018
DOI: 10.2147/nss.s127816
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tonsillectomy on obstructive sleep apnea: an overview of systematic reviews

Abstract: ObjectiveTonsillectomy with adenoidectomy is a combination surgery that has been used to treat pediatric obstructive sleep apnea (OSA). For adults, tonsillectomy has also been reported as a primary treatment modality when the tissue is hypertrophied. The objective of this study is to provide an overview of published systematic reviews and meta-analyses of tonsillectomy with or without adenoidectomy as used in the treatment of OSA in children and adults.Data sourcesNine databases, including PubMed/MEDLINE.Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…However, it is important to highlight the fact that MLS surgery has resulted in a dramatic reduction in AHI that allows us to examine the difference in metabolites before and after surgery. Given the fact that tonsillectomy is a very common surgical procedure, particularly in children, its utility in treating OSA (as it improves the airflow and improves breathing) is also combined with an improved metabolic status [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to highlight the fact that MLS surgery has resulted in a dramatic reduction in AHI that allows us to examine the difference in metabolites before and after surgery. Given the fact that tonsillectomy is a very common surgical procedure, particularly in children, its utility in treating OSA (as it improves the airflow and improves breathing) is also combined with an improved metabolic status [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the group of 15 patients with side effects after 24 months, the mean age was 52 years (range, 23-66 years), mean BMI was 28 kg/m 2 (range, 22-37 kg/m 2 ), mean AHI score was 28 (range, 2-78), and mean ESS score was 6 (range, [3][4][5][6][7][8][9][10][11][12][13][14][15]. This was compared with the group of 34 patients without side effects with a mean age of 43 years (range, 23-62 years), mean BMI of 28 kg/m 2 (range, 21.4-33.8 kg/m 2 ), mean AHI score of 22 (range, 0-78), and mean ESS score of 6 (range, 2-17).…”
Section: Degree and Types Of Side Effects After Surgerymentioning
confidence: 99%
“…Tonsillectomy alone has been shown in a review to be effective in patients with tonsil hyperplasia, 3 but long-term data to support tonsillectomy as a primary surgical treatment for adults with OSA are lacking. 4 There are alternative techniques to UPPP, such as lateral pharyngoplasty with myotomy and repositioning of the muscles of the lateral pharyngeal wall. 5 However, there is an increased risk of side effects and increased complication rate with extended surgery, and the evidence for a demonstrated effect on OSA from these surgical alternatives is still low, even in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…Another predisposing factor is adenotonsillar hypertrophy (AH), which is more frequent in preschoolers (3 to 5 years) [ 3 , 8 ]. Functional factors include neuromuscular diseases and nasal obstruction following viral infections [ 12 , 13 , 14 ]. Various studies have shown improvements in cognitive disorders after AT [ 15 ], probably before age 9, suggesting that the benefits of surgery decrease after this threshold age [ 16 ].…”
Section: Introductionmentioning
confidence: 99%